The age of fable--part 1 eaudiobook - Bulfinch, Thomas (Recorded Books Inc., 1995)
Ancient myths speak eloquently of the affairs of immortal gods and shining heroes, while linking us to our cultural history. Bulfinch captures these fables in one graceful, lyrical collection which has been an enduring success for over 140 years. Now, through George Guidall's lucid two-part narration, The Age of Fable takes on new life and power. Part One includes the fascinating tales of Prometheus, Hercules, and Ulysses. Part Two completes the collection with the adventures of aeneas, Thor, Beowulf, and other heroes.